MENINGKATKAN PRODUKSI KACANG ASIN DENGAN MESIN SANGRAI SEMI OTOMATIS - ATMIKA, IK ADI; SRI KOMALA DEWI, AA ISTRI AGUNG; NINDHIA, TG TIRTHA (Buletin Udayana Mengabdi; Vol 14 No 1 (2015): April 2015)
UD Mekar Sari and Bina Sejahtera group is facing a lot of problems to make their product, among others : 1) Oven Processing use the rolling machine which is relative modestly with small capacity. 2)Packing product which is manually done l by hand and use the candle to gum the plastic packer. 3)Mixturing flavour is also still manual so that is less flatten. Planning and making two semi-automatically machine dry-frying in order to have more amount and better results compared to the appliance use conventional machine. This was also giving the knowledge of appliance, working safety and operation of quality product. The Community service started from technical scheme and appliance making machine, then activity in field executed at 09 November 2013 for the recognition of appliance demonstration and also working safety recognition. This activity was conducted in desa Baluk, kabupaten Jembrana attended by 16 competitive people from various participants, among others : group member of Bina Sejahtera, team of community service, students of Mechanical Enginering Departement of University Udayana, some members from local society. The same activity, moreover was done in UD Mekar Sari on 12 November 2013. Keywords: UD Mekar Sari, Bina Sejahtera group, oven processing, small capacity